Variables That Best Differentiate In-Patient Acute Stroke from Stroke-Mimics with Acute Neurological Deficits - P. Natteru; M. R. Mohebbi; P. George; D. Wisco; J. Gebel; C. R. Newey (Stroke Research and Treatment)
Introduction. Strokes and stroke-mimics have been extensively studied in the emergency department setting. Although in-hospital strokes are less studied in comparison to strokes in the emergency department, they are a source of significant direct and indirect costs. Differentiating in-hospital strokes from stroke-mimics is important. Thus, our study aimed to identify variables that can differentiate in-hospital strokes from stroke-mimics. Methods. We present here a retrospective analysis of 93 patients over a one-year period (2009 to 2010), who were evaluated for a concern of in-hospital strokes. Results. About two-thirds (57) of these patients were determined to have a stroke, and the remaining (36) were stroke-mimics. Patients with in-hospital strokes were more likely to be obese (p=0.03), have been admitted to the cardiology service (p=0.01), have atrial fibrillation (p=0.03), have a weak hand or hemiparesis (p=0.03), and have a prior history of stroke (p=0.05), whereas, when the consults were called for “altered mental status” but no other deficits (p<0.0001), it is likely a stroke-mimic. Conclusion. This study demonstrates that in-hospital strokes are a common occurrence, and knowing the variables can aid in their timely diagnosis and treatment.